Engineering of superhydrophobic silica microparticles and thin coatings on polymeric films by ultrasound irradiation. (August 2021) - Iline-Vul, T.; Bretler, S.; Cohen, S.; Perelshtein, I.; Perkas, N.; Gedanken, A.; Margel, S.
Abstract: Superhydrophobic coatings are one of the recent hot topics in industrial applications as well as academic studies. The mimicking lotus leaves' superhydrophobic properties have been successfully transferred to real-life applications. However, the current preparation methods used to obtain superhydrophobic coatings are still complex, commonly are not transparent and/or not durable. In the present study, a new relatively simple way to prepare superhydrophobic coatings on polymeric films is described. First, superhydrophobic silica microparticles (MPs) were synthesized by fluorination of SiO2 MPs produced by a modified Stöber method. Briefly, tetraethyl orthosilicate was polymerized in an ethanol/water continuous phase under basic conditions, and the resultant SiO2 MPs were dispersed in heptane as a continuous phase and reacted with 1H, 1H, 2H, 2H-perfluorododecyltrichlorosilane (FTS) to yield FTS-SiO2 MPs, which were dried and dispersed in decane. Superhydrophobic thin coatings were then produced by a 'throwing stones' sonication technique and deposited onto polycarbonate, polypropylene, polyethylene, and polyurethane films. The coatings are durable, may be transparent, and exhibit self-cleaning properties for the specific practical applications. The MPs and coated polymeric films were characterized by dynamic light scattering, high-resolution scanning electron microscopy, water contact and sliding angle measurements, and infrared and x-ray photoelectron spectroscopy. This ultrasound-assisted coating process may be upscaled and applied to many polymeric films, for instance polymethyl methacrylate, polystyrene, and polyvinyl chloride. Various applications are envisaged, including but not limited to self-cleaning windows, anti-sticking of snow to antennas and windows, solar panels, roof tiles, agricultural applications, corrosion resistance, and anti-biofouling. Graphical abstract: Image 1 Highlights: Superhydrophobic silica microparticles (MPs) were synthesized by fluorination of SiO2  MPs produced by a modified Stöber method. Superhydrophobic thin coatings were produced by a 'throwing stones' sonication technique and deposited onto polymeric films. Adhesion of the 1H, 1H, 2H, 2H-perfluorododecyltrichlorosilane (FTS) -SiO2  MPs to the films, high durability, and good self-cleaning properties of the coatings were shown, which demonstrate their potential for various applications. FTS-SiO2  coating on the PC film showed excellent optical properties which can be applied to specific practical applications.